Transformation of the Position, Functions, and Authorities of the People’s Consultative Assembly in the Indonesian Constitutional System After the Amendment of the 1945 Constitution: Transformasi Kedudukan, Fungsi, Dan Kewenangan Majelis Permusyawaratan Rakyat Dalam Sistem Ketatanegaraan Indonesia Pasca Amandemen Uud 1945 - Mar'ah Shaliha; Muh. Reyhan Al Fauzi; Nur Aswini; Nur Azisa; Nur Maladewi; Firdaus; Andi Santri Syamsuri (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2026)
This article examines the changes in the position, functions, and role of the People’s Consultative Assembly (Majelis Permusyawaratan Rakyat/MPR) following the amendments to the 1945 Constitution of the Republic of Indonesia. This study employs a literature review method by analyzing constitutional law textbooks, academic journals, official MPR documents, and historical records of the reform era. Prior to the amendments, the MPR functioned as the highest state institution with extensive authority, including electing the President and Vice President and formulating the Broad Outlines of State Policy (GBHN) as national development guidelines. After the constitutional amendments, the MPR was transformed into a high state institution with a position equal to other state institutions, and its authority became more limited and focused, particularly on amending and enacting the Constitution, inaugurating the President and Vice President, and deciding on presidential dismissal under specific conditions based on decisions of the Constitutional Court. These changes represent not merely a reduction of authority but an effort to establish a more democratic and accountable constitutional system through the strengthening of the checks and balances principle. The findings indicate that despite its reduced authority, the MPR continues to play a crucial role in safeguarding constitutional continuity and symbolizing popular deliberation within Indonesia’s constitutional framework.